2020
DOI: 10.21037/jtd.2020.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided video-assisted thoracoscopic surgery with Artis Pheno for pulmonary nodule resection

Abstract: Contributions: (I) Conception and design: YF Cheng; (II) Administrative support: BY Wang; (III) Provision of study materials or patients: HC Chen;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Results published by Cheng et al's recent article "Imageguided video-assisted thoracoscopic surgery with ARTIS Pheno ® for pulmonary nodule resection" (18) are in line with the above mentioned studies. It is a retrospective analysis conducted in 2018 where 126 patients were divided equally and non-randomly into two groups.…”
Section: Editorialsupporting
confidence: 71%
See 1 more Smart Citation
“…Results published by Cheng et al's recent article "Imageguided video-assisted thoracoscopic surgery with ARTIS Pheno ® for pulmonary nodule resection" (18) are in line with the above mentioned studies. It is a retrospective analysis conducted in 2018 where 126 patients were divided equally and non-randomly into two groups.…”
Section: Editorialsupporting
confidence: 71%
“…Compared with its predecessor, ARTIS Pheno ® has a wider C-arm with 130 cm focalspot-to-detector distance that gives a usable clearance up to 95.5 cm. All patients in the study were set at true lateral decubitus position during both localization and surgery, without ensuing collision due to the longer radius of gyration provided by ARTIS Pheno ® (18). After localization, surgery can immediately start without the need for repositioning the patient.…”
Section: Editorialmentioning
confidence: 99%
“…The latter further, helps avoid collision of equipment and patients and enables the easier setting of the surgery. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the mean time from localization to skin incision was 23.57 minutes with iVATS. [10] The complication rate of iVATS is pretty low. We suggested that iVATS extended segmentectomy can create more resection margin and make a precise resection.…”
Section: Discussionmentioning
confidence: 99%
“…We describe a novel technique using image-guided video-assisted thoracoscopic surgery (iVATS) to accomplish extended segmentectomy. There were several studies that discussed the details of iVATS with cone-beam CT. [8][9][10] In this study, we aimed to compare the effects of iVATS extended segmentectomy and the effects of traditional segmentectomy for stage I NSCLC.We designed a retrospective study to nd out if iVATS extended segmentectomy can create more resection margin than traditional segmentectomy.…”
mentioning
confidence: 99%